THE INFLUENCE OF INDIVIDUAL RANK AND WORKING EXPERIENCE ON PROFESSIONALISM OF INTERNAL AUDITOR (Study on Internal Auditors of Public Corporation at Manufacturing Sector Listed in The Jakarta Stock Exchange) - Gunarianto Gunarianto (Journal of Economics, Business, and Accountancy Ventura, 2010)
One of the causes of economic crisis and failure experienced by a number of Indonesian companies is the corporate governance. If the internal audit can be properly implemented, it will contribute to improving the process of corporate governance, risk management, and management control. This research attempts to obtain empirical evidence and better understanding concerning: (1) ) the correlation between individual rank with working experience in manufacturing sector listed at the JSX; (2) the influence of individual rank and working experience on the internal auditors’ professionalism of public companies in manufacturing sector listed at the JSX either partially and simultaneously. The type of research employed in this study is causal relationship by using the census method for 120 internal auditors of public companies in manufacturing sector at the JSX. The data this study consist of both primary and secondary data. Reliability and validity tests were conducted to examine the questionnaires. SEM (Structural Equation Modeling) is used to examine the correlation as well as the effect of the variable. It was found that (1) there is correlation between individual rank and internal auditors’ working experience and between internal auditors’ working experience (R2 =0.52); (2) individual rank and working experience partially influence the internal auditors’ professionalism for with the levels of influence are 6%, and 20% respectively, whilst their simultaneous effect is 30%.